2015
DOI: 10.1080/02701367.2015.1078870
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Perceived Exertion in Constant-Power Cycling: Time- and Workload-Dependent Thresholds

Abstract: Time- and workload-dependent thresholds were revealed studying the PES dynamics in constant cycling. Monitoring PES can complement or provide an alternative to the use of physiological measures for an accurate control of training workloads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…During the later stages of effort, when approaching volitional exhaustion, there is a shift toward stable, nonfluctuating dynamics, specifically a continuous increase in RPE and task-related thoughts, which are associated with the imminent cessation of exercise. This shift from fluctuating to nonfluctuating dynamics is consistent with the previously reported attentional shift threshold (Hutchinson & Tenenbaum, 2007) and corresponds with the transition from heavy (RPE-15) to very heavy intensity exercise (RPE-17, using the 6-20 scale; Balagué et al, 2015).…”
Section: Dynamic Psychobiological Model Of Exercise-induced Fatiguesupporting
confidence: 89%
See 1 more Smart Citation
“…During the later stages of effort, when approaching volitional exhaustion, there is a shift toward stable, nonfluctuating dynamics, specifically a continuous increase in RPE and task-related thoughts, which are associated with the imminent cessation of exercise. This shift from fluctuating to nonfluctuating dynamics is consistent with the previously reported attentional shift threshold (Hutchinson & Tenenbaum, 2007) and corresponds with the transition from heavy (RPE-15) to very heavy intensity exercise (RPE-17, using the 6-20 scale; Balagué et al, 2015).…”
Section: Dynamic Psychobiological Model Of Exercise-induced Fatiguesupporting
confidence: 89%
“…Balagué and colleagues have conducted a series of studies examining the dynamics of perceived exertion and attention allocation during progressive exhaustive exercise. Findings from these studies have revealed a nonproportional effect of effort accumulation on thought dynamics (Balagué, Hristovski, Aragonés, & Tenenbaum, 2012) and perceived exertion shifts (Aragonés et al, 2013;Balagué et al, 2015). Two distinct phases have been identified during progressive exercise: a period of fluctuating dynamics and a period of dynamic stability.…”
Section: Dynamic Psychobiological Model Of Exercise-induced Fatiguementioning
confidence: 99%
“…Findings from research that focused on subjective experiences have revealed fluctuating and metastable dynamics inherent to effort perception and within different types of exercise setting (Balagué et al, 2012, 2015; Aragonés et al, 2013; Garcia et al, 2015; Slapsinskaite et al, 2016). Metastability can be seen as a property related to the existence of multiple separated timescales (Bovier and Den Hollander, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such strategies enable capture of the nonlinear dynamics of integrated variables (e.g., perceived exertion, volition states, attention focus) during exercise and may help to anticipate exhaustion and task failure. Effort phases defined by perceived exertion thresholds, informing about the time and workload intensities that can be sustained over time [ 118 ], have been detected and correlated with conventional physiological measures of anaerobic threshold [ 88 ]. Such ordinal and continuous recording strategies may solve one of the main limitations of subjective monitoring: to precisely transform the complex information of subjective perception(s) in oversimplified numbers [ 74 ].…”
Section: Subjective and Objective Sports Monitoring: Advantages And L...mentioning
confidence: 99%